Gestão do conhecimento: uma proposta de modelo para associações empresariais - Antochio, Marcela (2014)
In an environment where competitive advantage and taking appropriate decisions are essential to business success, the use of mechanisms that facilitate the storage and retrieval of informational sources and knowledge management can become an ally in the "race" by the market. In this scenario also, are micro and small enterprises, competing directly with companies of medium to large, national and international. How micro and small enterprises can reach levels of excellence and quality in their products and services when encountered a macroeconomic scenario so diverse? This research, using as a basis the state of the art in Knowledge Management, intends to structure a model of knowledge management that provides the generation and exchange of knowledge capable of external aid in the decision-making mechanism. For this exploratory research, a survey of secondary sources and primary data was performed. The proposed model aims to demonstrate the processes of knowledge generation, filtering, disclose, store and retrieve such knowledge, based on the characteristics and needs related to business associations and companies that integrate and propose mechanisms for analysis of the use in order to provide tools to classify the levels of improvement in organizational learning and performance together in the organization, is also defined the role of the participating members of the Association for each step, demonstrating the importance of the human factor for an effective Knowledge Management. , Filtering, DSI for businesses; Storage; Use, Decision Making, Organizational Performance and Professional Knowledge Generation of Knowledge: As a final result a model of knowledge management consists of 8 steps was obtained.